The reversible P2Y12 antagonist ACT‐246475 causes significantly less blood loss than ticagrelor at equivalent antithrombotic efficacy in rat. Issue 5 (13th August 2017) - Rey, Markus; Kramberg, Markus; Hess, Patrick; Morrison, Keith; Ernst, Roland; Haag, Franck; Weber, Edgar; Clozel, Martine; Baumann, Martine; Caroff, Eva; Hubler, Francis; Riederer, Markus A.; et al.
Abstract: The P2Y12 receptor is a validated target for prevention of major adverse cardiovascular events in patients with acute coronary syndrome. The aim of this study was to compare two direct‐acting, reversible P2Y12 antagonists, ACT‐246475 and ticagrelor, in a rat thrombosis model by simultaneous quantification of their antithrombotic efficacy and surgery‐induced blood loss. Blood flow velocity was assessed in the carotid artery after FeCl3 ‐induced thrombus formation using a Doppler flow probe. At the same time, blood loss after surgical wounding of the spleen was quantified. Continuous infusions of ACT‐246475 and ticagrelor prevented the injury‐induced reduction of blood flow in a dose‐dependent manner. High doses of both antagonists normalized blood flow and completely abolished thrombus formation as confirmed by histology. Intermediate doses restored baseline blood flow to ≥65%. However, ACT‐246475 caused significantly less increase of blood loss than ticagrelor; the difference in blood loss was 2.6‐fold ( P  < 0.01) at high doses and 2.7‐fold ( P  < 0.05) at intermediate doses. Potential reasons for this unexpected difference were explored by measuring the effects of ACT‐246475 and ticagrelor on vascular tone. At concentrations needed to achieve maximal antithrombotic efficacy, ticagrelor compared with ACT‐246475 significantly increased carotid blood flow velocity in vivo ( P  = 0.003), induced vasorelaxation of precontracted rat femoral arteries, and inhibited contraction of femoral artery induced by electrical field stimulation or by phenylephrine. Overall, ACT‐246475 showed a significantly wider therapeutic window than ticagrelor. The absence of vasodilatory effects due to high selectivity of ACT‐246475 for P2Y12 provides potential arguments for the observed safety advantage of ACT‐246475 over ticagrelor.